Reinventing two-spiritedness: Paula Gunn Allen's Ephanie and Louise Erdrich's Agnes/Father Damian - Bánovcová, Anna (2007)
This thesis deals with the concept of Two-Spiritedness in Paula Gunn Allen's The Woman Who Owned the Shadows and Louise Erdrich's The Last Report on the Miracles at Little No Horse. The thesis basically falls into two parts; in the first part I provide cultural and historical information for understanding the phenomena-I deal with the role of Christianity and the English language in the identity formation of Native Americans, particularly Two-Spirits. The next part is devoted to the role of language and literature and lastly provides the analysis of the two novels